Measured and predicted heat transfer coefficients for boiling zeotropic mixed refrigerants in horizontal tubes. (June 2016) - Barraza, Rodrigo; Nellis, Gregory; Klein, Sanford; Reindl, Douglas
Highlights: Heat transfer coefficients for boiling zeotropic mixtures of small horizontal tubes. Temperature glides include from cryogenic temperatures to room temperature. Sensitivity of the measured heat transfer coefficient are studied. Heat transfer coefficient of zeotropic mixtures are well predicted by Granryd. Abstract: The use of mixed gas working fluids has become common in Joule–Thomson type cryocoolers for a variety of applications. However, there is a scarcity of data currently available with supporting theory capable of predicting the heat transfer coefficients associated with two-phase, multi-component mixtures at cryogenic temperatures. This paper aims to fill this void by providing experimental data for the heat transfer coefficient associated with of multicomponent zeotropic mixtures boiling in small channels over temperatures ranging from 100 K to room temperature. The sensitivity of the measured heat transfer coefficient to parameters such as heat flux, mass flux, pressure, tube diameter, and mixture composition is also presented. The results indicate that the heat transfer process is driven, principally, by convective boiling; however, composition, diameter, and surface roughness affect the measured heat transfer coefficient. Evaporating pressure has less relevance compared to the other parameters. The actual experimental data collected as part of this effort and additional data from Nellis et al. (2005) are used to evaluate models to characterize the heat transfer process for boiling zeotropic mixtures in horizontal tubes. The heat transfer coefficient data is predicted well using correlations described by Granryd (1991) and Little (2008). The Granryd correlation is the recommended correlation to predict heat transfer coefficient of zeotropic mixtures because it shows the best accuracy with an Absolute Average Deviation (AAD) of 16% and predicts 83% of the data with a relative error lower than 25%. The Little correlation exhibits greater accuracy at high Reynolds number, high thermodynamic quality, or both; however, its accuracy is substantially reduced for low qualities and low Reynolds number.